Electrokinetic bioremediation technique on contaminated landfill soil by pseudomonas putida - Abdul Talib, Ain Nabila (2020)
Currently, many researchers are finding solutions to remediate heavy metal contamination in soil. The Electrokinetic Remediation (EK-R) treatment is one of the methods that can be used for the removal of heavy metals. By combining with other techniques such as Bioremediation would likely increase the effectiveness of the EK-R technique. The objective of this research is to investigate the ability of Electrokinetic Bioremediation (EK-Bio) technique to remove Hg, Cu, Zn, As, Pb, nitrate and sulphate from Bukit Bakri landfill soil at Muar, Johor. Pseudomonas putida (P.putida) was used in this research because it can survive easily under various conditions. P.putida was used in the EK-Bio technique as an agent to improve the performance of Hg, Cu, Zn, As, Pb, nitrate and sulphate removal from contaminated landfill soil. Research were conducted for durations of 1, 2, 3, 5, 7 and 14 days under low voltage (1 V/cm) and ambient temperature. The results showed that the EK-Bio treatment can remove up to 61 %, 95 %, 69 %, 71 % and 51 % of Hg, Cu, Zn, As and Pb respectively at distance of 3 cm from the anode. Meanwhile, 99.6 % and 98.5 % of nitrate and sulphate were removed respectively at a distance 15 cm from anode. Besides that, the enumeration of P.putida for all the EK-Bio treatments increased with the duration of treatment. Thus, this research showed that the EK-Bio treatment was able to increase the removal of Hg, Cu, Zn, As, Pb, nitrate and sulphate in contaminated landfill soil. It can be concluded that the EK-Bio treatment using P.putida potentially can be used to treat the contaminated soil.